2016
DOI: 10.1161/strokeaha.116.012650
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Restenosis Following Carotid Angioplasty and Stenting

Abstract: Background and Purpose-Restenosis after carotid angioplasty (with or without stent) is associated with increased rate of stroke and death. Our aim was to determine risk and predictive factors related to carotid restenosis post carotid angioplasty and its association to recurrent cerebrovascular events. Methods-All consecutive patients with carotid stenosis treated with angioplasty (n=1060) in a single University Hospital were included (from 2002 to 2013). Follow-up was done prospectively evaluating restenosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 10 publications
1
11
1
Order By: Relevance
“…Gutierrez et al [21] reported female sex and diabetes as risk factors for recurrent carotid artery stenosis after endarterectomy. In addition, results from other studies have shown that contralateral stenosis, and ASA grades 2 and 3 are independent predictors of carotid restenosis [22,23]. Our results were not in link with previous studies.…”
Section: Discussioncontrasting
confidence: 86%
“…Gutierrez et al [21] reported female sex and diabetes as risk factors for recurrent carotid artery stenosis after endarterectomy. In addition, results from other studies have shown that contralateral stenosis, and ASA grades 2 and 3 are independent predictors of carotid restenosis [22,23]. Our results were not in link with previous studies.…”
Section: Discussioncontrasting
confidence: 86%
“…Duplex ultrasonography also correlated very well with catheter-based angiography. Peak systolic velocity (PSV) of 300 cm/s, enddiastolic velocity (EDV) of 140 cm/s, and ICA/CCA of 3.8 are, as well, optimal cutoff points to detect 70% restenosis after stenting (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Zapata-Arriaza et al . [ 40 ] reported that hypertension and impaired vasoreactivity were independent risk predictors of restenosis (≥70%), though their cohort included only angioplasty cases without stents. Regarding characteristics of the original plaque, plaques longer than 20 mm were reported to be significantly related to restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent stenosis or in-stent restenosis after carotid artery stenting (CAS) is known as a risk factor of ipsilateral stroke, and this stroke risk should be monitored during patient follow-up. [ 22 23 24 ] Several factors related to post-CAS restenosis have been reported, including demography, comorbidity, and/or characters of original plaques, e.g., age,[ 4 22 ] female gender,[ 22 ] symptomatic cases,[ 13 ] diabetes,[ 5 22 ] hypertension,[ 22 40 ] hyperlipidemia,[ 22 ] inflammation markers,[ 37 ] high-degree stenosis,[ 32 ] and length of the plaques,[ 31 ] although some of these studies merely conducted univariate or combined analyses with restenoses after carotid endarterectomy (CEA). Several researchers reported CAS-procedure-related factors of post-CAS restenosis, such as immediate residual stenosis,[ 7 31 40 ] double stent deployment,[ 7 ] use of an open-cell stent,[ 20 ] and the predilation balloon diameter.…”
Section: Introductionmentioning
confidence: 99%